2015
DOI: 10.1155/2015/148680
|View full text |Cite
|
Sign up to set email alerts
|

MPPT of Magnus Wind System with DC Servo Drive for the Cylinders and Boost Converter

Abstract: This paper presents an algorithm MPPT (Maximum Power Point Tracking) for a Magnus wind system with a DC servo drive system (DC drive and BLDC motor) to rotate the turbine cylinders. The optimal cylinders rotation is the one to deliver the maximum power extracted from the wind tracked by fixed and adaptive step HCC (Hill Climbing Control) acting on the servo drive. The proposed wind system consists of a PMSG (Permanent Magnet Synchronous Generator), a three-phase diode rectifier, a DC/DC (boost) converter, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…The third scientific group managed by Maro Jinbo focused its efforts on developing control systems of MWT [15,16]. They concluded that the most efficient approach is the maximum power point tracking (MPPT), based on the hill-climbing control algorithm (HIL) [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The third scientific group managed by Maro Jinbo focused its efforts on developing control systems of MWT [15,16]. They concluded that the most efficient approach is the maximum power point tracking (MPPT), based on the hill-climbing control algorithm (HIL) [15].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the background, the authors designed an algorithm and method to realize the fixed-step HIL algorithm for MWT. The expanded description of the HIL algorithm was described in [16]. That paper focused on algorithm practical realization.…”
Section: Introductionmentioning
confidence: 99%